(untitled) (Journal of Atomic and Molecular Sciences, 2010)
Close to converged energies and wave functions for the positron binding systems, LiPs and e^+Be are computed using the stochastic variational method. Binding energies and annihilation rates from both ab-initio and fixed core calculations are determined and found to be in agreement. The ab-initio binding energy of e^+Be was 0.00316 Hartree while that for LiPs was 0.01237 Hartree.